Pengendalian Waktu dan Biaya dengan Metode Earned Value Analysis (Studi Kasus: Rekonstruksi Jalan Kabupaten Kutai Kartanegara) - Dharwati P. Sari; Bernardo Sandrini Salasa (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
This research aims to describe the effect of changing control of the reconstruction on Sangasanga-Dondang road, Kutai Kartanegara Regency that have an impact on the time and cost. The length of the road is ± 18.02 km, starting from the intersection of three Sanga Sanga sub-districts and ending at the Dondang Bridge. The road often receives traffic loads from light vehicles and heavy vehicles. This disrupted the stability of the road structure so that some of the road segments experienced structural damage.This research used Earned Value Analysis (EVA), this method used three paramaters, namely Planned Value (PV), Earned Value (EV), and Actual Cost (AC). Based on analysis that had been done when a deviation occurs at estimate the project completion time for 36 weeks. From the parameters, the result obtained were earned value analysis was carried out in 2 weeks with BCWS value of Rp. 73,628,055.56, BCWP value of Rp. 214,691,666.67, and the ACWP value is Rp. 15,099,335,843.68.